Alexander Betancourt Mendieta, Historia, ciudad e ideas. La obra de José Luis Romero. México, Universidad Nacional Autónoma de México, 2001. 198 pp. - Cattaruzza, Alejandro (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2004)